Angelika Molnár: Reception and Analysis of the Text. Selected works. Moscow, Azbukovnik, 2023, 447 pp. ISBN 978-5-91172-236-4 - S. Horváth, Géza (Slavica, 2024)
The review examines a new book by Hungarian researcher Angelika Molnár on classical Russian literature of the 19th century. Molnár’s book analyses the works of Pushkin, Lermontov, Turgenev, Tolstoy and Chekhov in the context of the overlaps with the literature of the 21st century (Ulitskaya, Akunin, etc.). The main emphasis is placed on describing the principles of textual formation through the prism of discursive poetics. The history of Hungarian reinterpretation of Russian classics is widely represented in the book. The interpretations of the works reveal unusual correlations between the works and show the specificity of the writers’ poetics in a new way.